2005
DOI: 10.1093/jxb/eri147
|View full text |Cite
|
Sign up to set email alerts
|

The stoichiometry and antenna size of the two photosystems in marine green algae, Bryopsis maxima and Ulva pertusa, in relation to the light environment of their natural habitat

Abstract: The stoichiometry and antenna sizes of the two photosystems in two marine green algae, Bryopsis maxima and Ulva pertusa, were investigated to examine whether the photosynthetic apparatus of the algae can be related to the light environment of their natural habitat. Bryopsis maxima and Ulva pertusa had chlorophyll (Chl) a/b ratios of 1.5 and 1.8, respectively, indicating large levels of Chl b, which absorbs blue-green light, relative to Chl a. The level of photosystem (PS) II was equivalent to that of PS I in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 21 publications
7
37
0
1
Order By: Relevance
“…This interpretation of the 77 K fluorescence emission of the brackish ecotype of F. vesiculosus in Gylle et al (2011) appears to be in line with the immunoblot signals of D1/PsaA (Table 1). The PSII/PSI ratio differ between different organisms and have been observed to be 1.43-1.72 in some terrestrial plants, 0.43 in blue-green algae and 0.84-1.03 in some green algae (Melis & Brown, 1980;Falkowski et al, 1981;Yamazaki et al, 2005;Fan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation of the 77 K fluorescence emission of the brackish ecotype of F. vesiculosus in Gylle et al (2011) appears to be in line with the immunoblot signals of D1/PsaA (Table 1). The PSII/PSI ratio differ between different organisms and have been observed to be 1.43-1.72 in some terrestrial plants, 0.43 in blue-green algae and 0.84-1.03 in some green algae (Melis & Brown, 1980;Falkowski et al, 1981;Yamazaki et al, 2005;Fan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also spectral changes can affect light absorption by altering the composition and ratio of the two photosystems (PSs) and, thus, photosynthetic rates and plant growth (Fujita 1997;Falkowski and Raven 2007). Among marine macrophytes, such spectral changes were shown to influence the functionality of the two PSs as found for the green macroalgae Ulva pertusa and Bryopsis maxima (Yamazaki et al 2005). Regarding seagrasses, only two studies have reported on changes in the PS composition: one in shallow-growing plants during various seasons (Major and Dunton 2000) and another along a narrow depth gradient down to 1.6 m (Major and Dunton 2002).…”
mentioning
confidence: 99%
“…It has been shown that shade tolerant species produce a higher proportion of chlorophyll b relative to chlorophyll a, which leads to a lower chlorophyll a/b ratio, to enhance the efficiency of blue light absorption in low light environments (Yamazaki et al, 2005). Forest mosses in the present study responded in the opposite direction.…”
Section: Discussionmentioning
confidence: 46%